Different Mechanisms of DNA Radiosensitization by 8-Bromoadenosine and 2'-Deoxy-2'-fluorocytidine Observed on DNA Origami Nanoframe Supports - Sala, Leo; Lyshchuk, Hlib; Šáchová, Jana; Chvátil, David; Kočišek, Jaroslav (The journal of physical chemistry letters, 2022)
DNA origami nanoframes with two parallel DNA sequences are used to evaluate the effect of nucleoside substituents on radiation-induced DNA damage. Double strand breaks (DSB) of DNA are counted using atomic force microscopy (AFM), and total number of lesions is evaluated using real-time polymerase chain reaction (RT-PCR). Enhanced AT or GC content does not increase the number of DNA strand breaks. Incorporation of 8-bromoadenosine results in the highest enhancement in total number of lesions; however, the highest enhancement in DSB is observed for 2'-deoxy-2'-fluorocytidine, indicating different mechanisms of radiosensitization by nucleoside analogues with the halogen substituent on base or sugar moieties, respectively. "Bystander" effects are observed, when the number of DSB in a sequence is enhanced by a substituent in the parallel DNA sequence. The present approach eliminates limitations of previously developed methods and motivates detailed studies of poorly understood conformation or bystander effects in radiation induced damage to DNA.
Keywords: DNA Repair; poškození DNA; DNA; DNA Damage; Adenosine; deoxycytidin; Deoxycytidine; adenosin; oprava DNA